2007
DOI: 10.1111/j.1365-2702.2007.01665.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hand‐washing teaching programs for families of children in paediatric intensive care units

Abstract: The education program is a simple, low-cost, low technology intervention for substantially reducing the incidence of nosocomial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
3
20
0
5
Order By: Relevance
“…As nurses have been considered facilitators of care, whereas parents are seen as the ‘doers’ of care (Coyne & Cowley 2007) it makes sense to involve parents in increasing hand hygiene compliance. Accordingly, Chen and Chiang (2007) implemented a video‐centred teaching programme aimed at parents to increase their hand hygiene compliance in a paediatric intensive care unit, which resulted in higher compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As nurses have been considered facilitators of care, whereas parents are seen as the ‘doers’ of care (Coyne & Cowley 2007) it makes sense to involve parents in increasing hand hygiene compliance. Accordingly, Chen and Chiang (2007) implemented a video‐centred teaching programme aimed at parents to increase their hand hygiene compliance in a paediatric intensive care unit, which resulted in higher compliance.…”
Section: Discussionmentioning
confidence: 99%
“…2010) of hand hygiene compliance studies conducted in hospitals concluded that non‐compliance is a universal problem. As hand hygiene compliance is associated with healthcare‐associated infections (HCAIs) (Chen & Chiang 2007), this remains a cause for concern. However, although hand hygiene compliance is a relatively easy physical task and is also cheap, it appears that compliance to guidelines is complex and is dependent on behavioural determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has been conducted on strategies to encourage patients to wash their own hands more often 103e107 or persuade family/friends to wash their hands. 108 Strategies encouraging patients to ask HCPs about their HH could therefore usefully target patients' (and families') hand sanitation practices.…”
Section: Accessibility Of Strategiesmentioning
confidence: 99%
“…30 Chen and Chiang compared the use of a hand hygiene video and illustrated posters to teach hand hygiene to parents of pediatric intensive care patients and to empower them about their role in hand hygiene. 31 They reported a steady sustained increase in parents' compliance and empowerment using both educational strategies. These results were attributed to a strong motivation to protect their child.…”
Section: Educational Programsmentioning
confidence: 99%